(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Financial crimes have existed since the beginning of trade and commerce. The division of company ownership and management is a central contributor to the prevalence of economic crimes in the corporate environment. The criminalisation of commercial activities presents complex challenges for legal practitioners and businesses. This study contributes to the existing literature by comprehensively analysing criminalisation trends in commercial law, drawing upon empirical data from multiple jurisdictions and sectors. This article investigates the theoretical underpinnings and practical consequences of criminalising commercial activity, specifically its effects on business operations and market efficiency. This research examines criminalisation trends, outcomes, and efficacy in commercial law across various jurisdictions. This study employs a mixed-methods research design combining quantitative and qualitative approaches to examine criminalisation trends in commercial law. The research utilises a sequential explanatory design, where quantitative data collection and analysis are followed by qualitative inquiry to provide deeper insights into the observed patterns. The study reveals significant trends in the criminalisation of commercial law over the past decade, with important implications for legal practice and corporate governance. A steady increase in criminalisation rates may influence corporate decision-making more significantly than previously recognised, particularly given the reputational risks associated with criminal charges. International implications deserve careful consideration, especially given the global nature of modern commerce. The trend toward criminalisation in commercial law appears likely to continue, necessitating adaptation by both legal practitioners and corporate entities. While our findings support the strategic use of criminal sanctions in specific contexts, they also highlight the need to calibrate enforcement carefully approaches to maximise deterrence while minimising market disruption.